Disperse reinforced concrete: composition-structure-properties correlations - Marin Amareanu; Larisa Melita (Građevinar)
This study focuses on the influence of metal fibres on the physical and mechanical properties of dispersed reinforced concrete with additions. The final aim is to design and obtain high-performance concrete. Mechanical strength is not always the primary requisite imposed on high-quality concrete. However, the durability provided by very low permeability and aggressive environment resistance can lead to high-performance concrete. Fly ash, granulated blast-furnace slag, and microsilica were used for concrete preparation, and metal fibres were used for disperse reinforcement. The effects of these additions and the presence of steel fibres are used to increase concrete ductility, its ability to absorb energy (to increase mechanical strength), and the improvement of general durability.